Application of Response Surface Method in Optimization of Medium Composition for Xylanase Production by Bacillus halodurans CM1 in Submerged Fermentation - SARA GUSTIA WIBOWO; IS HELIANTI; ANI SURYANI; BUDIASIH WAHYUNTARI (Indonesian Society for microbiology, 2016)
A two level factorial design was performed to optimized xylanase production by alkalothermophilic Bacillus halodurans CM1 using response surface method. The variables involved in this experiment were carbon (X), 1 nitrogen source (X) concentration, and pH (XCorn cob and fish powder were use as carbon and nitrogen source 2 3 respectively. Statistical analysis of the experimental results in the range studied, only carbon source gave significant effect on xylanase production. Â A second-order model was proposed to represent the enzyme activity as a function of xylan concentration (X) and pH (X). Â The optimum corn cobs concentration was 4.37% (w/v), 1 3 fish powder P concentration was 1.75% (w/v) and pH 9. These conditions were tested and validated experimentally since the maximum growth rate achieved with these parameters, and the highest xylanase activity.